The Mango’s Mistletoe Leaves Extract Ameliorates Lupus by Inhibiting the Anti-dsDNA Antibody Production, the Percentages of CD8+CD28− and CD4+CD28− T Cells - Handono, Kusworini; Sunarti, Sri; Pratama, Mirza Zaka; Hidayat, Saiful; Solikhin, Muhammad Badrus; Sermoati, Inmas Andi; Yuniati, Maria Gabriela (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: In SLE patients, repeated antigen stimulations induce a progressive reduction in CD28 expression on the surface of T cells and the chronic inflammation condition. Mango’s mistletoe is a parasitic plant that has anti-inflammation, antiproliferation, and immunomodulatory activities. AIM: This study aimed to investigate the effect of mango’s mistletoe leaves extract (MLE) in inhibiting anti-dsDNA antibodies and ameliorating the percentages of CD8+CD28− and CD4+CD28− T cells in a pristane-induced lupus mice model. METHODS: Lupus induction was undertaken by an injection of pristane 0.5 ml intraperitoneally in 6–8-week-old female balb/c mice. Mice with lupus signs were grouped randomly into the treatment groups which received MLE at doses of 150, 300, and 600 mg/kgbw/d for 28 days, respectively, and the positive control group without MLE. On day 29, anti-dsDNA antibody levels were analyzed using an ELISA. One of the immunosenescence markers (CD28− T cells) was investigated using a flow cytometer. ANOVA test was used for statistical analysis. RESULTS: The mango’s mistletoe leaves extract (MLE) significantly decreased the number of anti-dsDNA antibodies (*p < 0.05), the percentages of CD8+CD28− T cells (*p < 0.05) and CD4+CD28− T cells (*p < 0.05). CONCLUSION: We resume that the mango’s mistletoe leaves can ameliorate lupus by inhibiting anti-dsDNA antibody production and the percentages of CD8+CD28− and CD4+CD28− T cells.